Challenges and Strategies in Dealing Children with Autism Spectrum Disorder: A Literature Review - Nisa, Lutfi Khoirun; Perdani, Roro Rukmi Windi; Graharti, Risti; Wardhani, Dyah Wulan Sumekar Rengganis; Fiana, Dewi Nur; Rahmayani, Fidha (CV. Jasa Sukses Abadi, 2025)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder that affects children permanently. The exact cause of GSA is not yet known and affects more men than women with a ratio of 4:1. This autism disorder in children appears from birth or a few months after birth, but is often diagnosed when the child is less than 3 years old. Confirmation of GSA diagnosis can use two screening tools, namely DSM-5 and M-CHAT. The management that can be given to children with GSA can be pharmacological and non-pharmacological treatment. According to the World Health Organization (WHO) in 2022, 1 in 100 children in the world is diagnosed with autism. Children with GSA have many disorders that can affect their daily activities, both verbally and non-verbally. The main symptoms that are often encountered in children with GSA are difficulties in social interaction, problems in communication, including difficulty learning language or abnormalities in speech, and a tendency to be obsessive about maintaining a consistent daily routine and environment. The prognosis of GSA depends on the severity of each individual and the accompanying disease. This of course makes parents who have children with GSA will be faced with specific challenges in raising their children because children with GSA have different characteristics. Effective strategies that can be carried out to improve disorders in GSA children include the use of visual aids, the creation of a structured daily schedule, good interpersonal communication, the application of the Applied Behavior Analysis (ABA) method, integrated sensory therapy, occupational therapy, and play therapy. In addition, to overcome the stress experienced by parents of children with GSA, especially in mothers, it can be done by providing parenting education through psychoeducation.